Quantitative and qualitative genomic characterization of cultivated Ilex L. species - Gottlieb, Alexandra Marina (2014)
The development of modern approaches to the genetic improvement of the tree crops Ilex paraguariensis (‘yerba mate’) and Ilex dumosa (‘yerba señorita’) is halted by the scarcity of basic genetic information. In this study, we characterized the implementation of low-cost methodologies such as representational difference analysis (RDA), single-strand conformation polymorphisms (SSCP), and reverse and direct dot-blot filter hybridization assays coupled with thorough bioinformatic characterization of sequence data for both species. Also, we estimated the genome size of each species using flow cytometry. This study contributes to the better understanding of the genetic differences between two cultivated species, by generating new quantitative and qualitative genome-level data. Using the RDA technique, we isolated a group of non-coding repetitive sequences, tentatively considered as Ilex-specific, which were 1.21- to 39.62-fold more abundant in the genome of I. paraguariensis. Another group of repetitive DNA sequences involved retrotransposons, which appeared 1.41- to 35.77-fold more abundantly in the genome of I. dumosa. The genomic DNA of each species showed different performances in filter hybridizations: while I. paraguariensis showed a high intraspecific affinity, I. dumosa exhibited a higher affinity for the genome of the former species (i.e. interspecific). These differences could be attributed to the occurrence of homologous but slightly divergent repetitive DNA sequences, highly amplified in the genome of I. paraguariensis but not in the genome of I. dumosa. Additionally, our hybridization outcomes suggest that the genomes of both species have less than 80% similarity. Moreover, for the first time, we report herein a genome size estimate of 1670 Mbp for I. paraguariensis and that of 1848 Mbp for I. dumosa.